1996
DOI: 10.1088/0953-8984/8/19/012
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of the magnetic properties of and its hydrides

Abstract: Self-consistent, general potential, electronic structure calculations have been performed for the Laves phase compound YMn 2 and its hydrides YMn 2 H x (x = 0.5 and 1.0). The parent material, YMn 2 , is found to be an itinerant antiferromagnet with a magnetic moment of 2.6µ B per Mn atom whereas for the hydrides an additional ferrimagnetic component appears. This is in good agreement with experiment. The dependence of the calculated atom-projected magnetic moments and hyperfine fields on the Mn-H interaction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…This is obviously connected to the H concentration, and for a better understanding of the magnetic properties, the e!ect of "lling the 3d band with electrons coming from the hydrogen should be considered. Band structure calculations (19) have shown that for YMn hydrides, an additional ferrimagnetic component must appear. Unfortunately, such calculations do not make it possible to explain the collinear or noncollinear behavior of the magnetic structure.…”
Section: Discussionmentioning
confidence: 99%
“…This is obviously connected to the H concentration, and for a better understanding of the magnetic properties, the e!ect of "lling the 3d band with electrons coming from the hydrogen should be considered. Band structure calculations (19) have shown that for YMn hydrides, an additional ferrimagnetic component must appear. Unfortunately, such calculations do not make it possible to explain the collinear or noncollinear behavior of the magnetic structure.…”
Section: Discussionmentioning
confidence: 99%
“…Main features are the same, but their shapes differ that is a result of different number of H atoms in close distance from the particular Mn atom. Pajda et al [1] suggested that H atoms acted as donors in the YMn 2 H x compounds for x = 0.5 and 1 because in their calculations the Fermi energy was slightly rising upon hydrogenation. In our case, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…fications for the Laves phase of RMn 2 compounds. Such DOS calculations were previously done by Pajda et al [1] for YMn 2 H x (x = 0.5 and 1). Here we present our calculations for this hydride with higher hydrogen content (x = 1.5, 2, 2.5 and 3).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Then, a conciliatory scheme to account for the anomalous behavior of the YMn 2 upon chemical substitution of Mn or interstitial hydrogen doping can be obtained in terms of the interplay of both the increase in the Mn-Mn distance and the electronic modification induced by chemical substitution into the DOS modification. 15,16 Trying to obtain a deeper insight into the mechanisms responsible for the unusual response of YMn 2 to external parameters we have tailored a series of Y 1Ϫx Ce x Mn 2 hydrides. As the electronic state of cerium is very sensitive to hydrogen absorption, the DOS of the system would become even more dependent on the Mn-H hybridization due to the existence of the Mn(3d)-Ce(5d) hybridization.…”
mentioning
confidence: 99%
“…In particular, Pajda et al have recently revealed the existence of a competition between the Mn-H hybridization, favoring reduced Mn magnetic moments, and the increased lattice constants producing larger Mn moments. 16 Within this framework, the presence of cerium is of particular significance because of the peculiar magnetic behavior of the CeM 2 systems (M ϭ3d transition metal͒. This depends on the strength of the hybridization between the d states of the transition metal and the cerium 4 f and 5d states.…”
mentioning
confidence: 99%